Parenting Difficult Children: Strategies for Parents of Preschoolers to Preteens - Hammond, Michael (Rowman & Littlefield Publishers, 2014)
Parenting young children is a challenge, and dealing with difficult or problem behavior can set up an atmosphere of tension and strife—not just between the child and the parents, but between parents as well. Parenting Difficult Children provides a method of removing that tension with specific strategies for parents of children age three to twelve who are exhibiting difficult or common negative behaviors. Here, a seasoned psychologist uses the expertise he’s attained through decades of clinical practice to provide parents with a practical and realistic approach to dealing with young children in order to extinguish negative behaviors and forge a stronger and more loving bond between parent and child. Using stories from his practice, coupled with the received knowledge of his field, he explores those actions and behaviors that result in more disciplined children, and happier families. Part one includes specific instruction on building a secure foundation of rules, discipline methods, communication skills, conflict resolution skills, and reinforcers for positive, desired behavior. Part two focuses on problem behaviors and what to do about them. Millions of parents of young children around the world crave detailed, specific, behavioral interventions that can be easily understood and applied to ensure great parenting success. They will find a good start in these pages.